Peran Kepemimpinan Pendidikan Dalam Membangun Ideologi Di Pondok Pesantren Darul Falah Ponorogo - Iqbal Fitriansyah (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract : The purpose of this study is to describe the role of educational leadership in building the ideology of education and the ideology of education built at the Darul Falah Islamic boarding school in Ponorogo. The results of this study found several findings about the ideology of education that was built. 1. The ideology built at the Darul Falah Islamic boarding school is the ideology of moderate education by adhering to the rules of education that have been outlined by the founder since the founding of the pesantren. The rule is